Identification as an Indicator of Social Entropy Under Globalization: Ukrainian Realities and International Context - Ishchenko, Ihor; Bashkeieva, Olena; Zinukova, Nataliia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
The purpose of the article is to show modern trends in identification in the context of globalization and the specific conditions of political and economic systems, to indicate ways of influencing their formation, to change the value paradigm of identification associated with harmonious human relations. А hypothesis is that modern identification in Ukraine does not correspond to the liberal-democratic tradition and will continue to generate conflict. The existing identification structure should be used to reorient individuals and groups to effective communication within organizations, which will contribute to the political stability and security of the state. The following approaches and research methods have been used as tools to achieve this purpose: synergetic method; the reflective method; the dialectical method; a comparative method; structural-systemic method; synthesis method. The article covers the following issues: Analysis of identification models; Features of the identification mechanism in post-soviet realities; Modern synergetic model of identification in Ukraine; Peculiarities of culture formation in the conditions of digital and socio-cultural globalization; A new approach to identification as a factor of political stability and security. The authors made the following conclusions: The “ethnic model” of identification turns into a strange attractor, resulting in the Ruelle-Takens scenario. According to the theory of synergetics, this scenario became possible after three bifurcations in the political and economic system of Ukraine over the past 29 years. The “turquoise paradigm” elements should be taken as a basis for model of national identity.

Celem artykułu jest przedstawienie aktualnych trendów identyfikacji w kontekście globalizacji i specyficznych warunków systemów politycznych i gospodarczych, wskazanie sposobów wpływu na ich kształtowanie, zmiana paradygmatu wartościowego identyfikacji związanego z harmonijnymi relacjami międzyludzkimi. Hipoteza polega na tym, że współczesna identyfikacja na Ukrainie nie odpowiada tradycjom liberalno-demokratycznym i nadal będzie generować konflikty. Istniejące ramy identyfikacji powinny być wykorzystywane do reorientacji poszczególnych osób i grup na skuteczną komunikację w organizacjach, co przyczyni się do stabilności politycznej i bezpieczeństwa państwa. Jako narzędzia do osiągnięcia tego celu zastosowano następujące podejścia i metody badawcze: metodę synergiczną; metodę refleksyjną; metodę dialektyczną; metodę porównawczą; metodę strukturalno-systemową; metodę syntezy. W artykule omówiono następujące zagadnienia: analizę modeli identyfikacji; cechy mechanizmu identyfikacji w realiach postsowieckich; nowoczesny synergiczny model identyfikacji na Ukrainie; cechy kształtowania kultury w warunkach globalizacji cyfrowej i społeczno-kulturowej; nowe podejście do identyfikacji jako czynnika stabilności politycznej i bezpieczeństwa. Autorzy wyciągnęli następujące wnioski: „Model etniczny” identyfikacji przekształca się w dziwny atraktor, w wyniku czego powstaje scenariusz Ruelle-Takensa. Zgodnie z teorią synergii scenariusz ten stał się możliwy po trzech rozwidleniach w systemie politycznym i gospodarczym Ukrainy w ciągu ostatnich 29 lat. Elementy „paradygmatu turkusowego” należy traktować jako podstawę modelu tożsamości narodowej.
Identyfikacja jako wskaźnik entropii społecznej w warunkach globalizacji: ukraińskie realia i kontekst międzynarodowy
Keywords: identification; security; burification; synergetics; attractor; national identity models; turquoise paradigm; culture; globlization; identyfikacja; bezpieczeństwo; bifurkacja; synergetyka; atraktor; modele tożsamości narodowej; paradygmat turkusowy; kultura; globalizacja